Emissions of Air Toxic Compounds in Mobile Source for the Greater Metropolitan Area of Costa Rica in 2007 - Rodríguez-Yáñez, Javier E. (2015)
We estimated emissions of toxic compounds generated by the vehicle fleet in the GAM for 2007. This calculation was performed using emission factors obtained with the model of the EPA MOBILE 6 and activity data provided by the Energy Sector Management and the Ministry of Public Works and Transportation. Of the total 914,486 tons emitted by mobile sources of toxic pollutants evaluated, we have that 46% is associated with Benzene and Formaldehyde 26.8%. The emissions are mainly caused by private cars and light duty cargo or minibuses of gasoline powered, which represent 70% of total emissions.